2003
DOI: 10.1385/mo:20:1:13
|View full text |Cite
|
Sign up to set email alerts
|

Nasal NK/T-Cell Lymphoma with Disseminated Disease Treated with Aggressive Combined Therapy

Abstract: Thirty-two patients with nasal NK/T-cell lymphoma and disseminated disease (lung, skin, and bone marrow) were treated with an intensive combined therapy that consisted of three cycles of CMED (cyclophosphamide 2 g/m(2), metothrexate 200 mg/m(2), etoposide 600 mg/m(2), and dexamethasone 80 mg/m(2) with leucovorin rescue administered 24 h after) every 14 d, following high-dose radiotherapy: 55 Gy in 20 sesions to centrofacial region and three cycles more of the same chemotherapy regimen. To ameliorate the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…First, a Mexican group reported the results of a clinical study for newly diagnosed advanced nasal NKTCL [50]. There are no descriptions of the rationale for the planned sample size in their report.…”
Section: Clinical Trials In the Early 2000smentioning
confidence: 99%
“…First, a Mexican group reported the results of a clinical study for newly diagnosed advanced nasal NKTCL [50]. There are no descriptions of the rationale for the planned sample size in their report.…”
Section: Clinical Trials In the Early 2000smentioning
confidence: 99%
“…Regardless of the primary location, extranodal NK/T cell lymphoma presents as localized disease in approximately two thirds of patients [6,12]. Local extension of the tumor is more common than distant involvement and regional lymph node spread is a common occurrence [6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Local extension of the tumor is more common than distant involvement and regional lymph node spread is a common occurrence [6,18]. Dissemination of NK/T cell lymphoma is rare and appears to be organ specific, with the most commonly involved secondary sites being the skin, gastrointestinal tract, liver, bone marrow, and central nervous system [6,9,10,18]. Lung involvement by NK/T cell lymphoma is very rare and most commonly occurs with widely disseminated disease [6,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 108 patients with early-stage ENKL receiving radiotherapy followed by chemotherapy consisting with cyclophosphamide, epirubicin, vincristine, prednisolone, and bleomycin [Avilés et al, 2003], combined therapy demonstrated high efficacy with a 92% overall response rate and 8-year OS of 86%. In early-stage ENKL, Guo et al reported that patients who received CHOP followed by radiotherapy (45 Gy) had a CR rate of only 49% as compared to 100% for those who received radiotherapy prior to CHOP [Guo et al, 2008].…”
Section: Combined Modality Therapymentioning
confidence: 99%